ChemInform Abstract: An Expedient Synthesis of Cinnamyl Fluorides from Morita—Baylis—Hillman Adducts. Issue 40 (12th September 2013) - Lim, Cheol Hee; Kim, Se Hee; Lee, Hyun Ju; Kim, Hyung Jin; Kim, Jae Nyoung
Abstract The bromides (I) are synthesized by literature‐known procedures from Morita—Baylis—Hillman‐alcohols by treatment with HBr or PBr3.